Correlation of Tumor Marker Cancer Antigen (CA-125) against Hemoglobin, Leucocytes, and Platelet Lymphocyte Ratio in Ovarian Cancer Patients at RSUD ULIN Banjarmasin - sabarudin, hermin (Universitas Wijaya Kusuma Surabaya, 2018)
CA-125 is the most commonly used tumor marker in ovarian cancer, its known as the